Camphor Seed Kernel Oil Beneficial Effects the Gut Microbiota of the Non-Alcoholic Fatty Liver Disease Mice - Baogui Wang; Jun Wang; Wen Du; Shuai Shang (Frontiers in Bioscience-Landmark, 2022)
Introduction: Non-alcoholic fatty liver disease (NAFLD) has become one of the most common liver diseases globally and its negative impact has grad- ually attracted attention. Method: In order to explore whether camphor seed oil has a certain link effect on NAFLD, we identified its remodeling of intestinal flora and liver function index through the use of camphor seed kernel oil as food treatment (CCSKO). Results: Our results showed that camphor seed oil significantly improved the liver index, TG content and histopathology of the NAFLD mice compared with other groups. Meanwhile, we found significant differences in the intestinal microbiota of mice in different treatment groups. Discussion: The CCSKO treatment might significantly increase the abundance of Bacteroidetes, which were involved in many important metabolic activities in the human colon, including carbohydrate fermentation, utilization of nitrogenous substances, and biotransformation of bile acids and other steroids. Conclusions: These findings indicate a strong contribution in shaping the gut microbiota by treatment groups, shedding light on the impact of camphor tree seed kernel oil on gut microbiota.